Qualitative methods in rehabilitation research - Hagner, David C. [Verfasser]; Helm, David T. [Verfasser] (My University, 1994)
"Quantitative and qualitative research approaches each play a significant role in the development of knowledge, strategies, and public policy in the field of vocational rehabilitation. Qualitative methodologies in general, however, are less well understood than are quantitative methodologies, and qualitative research is sometimes viewed as more mysterious or less 'scientific' than is quantitative research. The authors outline the major features of qualitative research methods and the rehabilitation research context for which these methods are particularly appropriate. Representative examples of qualitative rehabilitation research are presented. Strategies for handling threats to reliability and validity within the qualitative tradition and criteria for assessing the adequacy of a qualitative study are presented." (author's abstract, IAB-Doku) ((en)) Die Autoren untersuchen die Bedeutung qualitativer Methoden im Rahmen der Erforschung beruflicher Rehabilitationsprozesse. Sie kommen zu dem Schluss, dass qualitative und quantitative Methoden einander ergänzen und beide eingesetzt werden sollten. (IAB)
Qualitative Methoden der Rehabilitationsforschung
Keywords: G 1.3.3.4 Wiedereingliederung; G 2.3.1 Arbeitsteilung & -organisation; G 1.2.4.2.8 Gesundheits-, Veterinär- und Sozialwesen; T 4.8 Arbeitswissenschaften; L 6 Qualität; Berufliche Rehabilitation; Rehabilitationsforschung; Qualitative Methode